1H-Pyrrole-2,5-dicarboxylic acid, a quorum sensing inhibitor from one endophytic fungus in Areca catechu L., acts as antibiotic accelerant against Pseudomonas aeruginosa - Liu, Junsheng; Wang, Zhennan; Zeng, Yuexiang; Wang, Wei; Tang, Shi; Jia, Aiqun (Frontiers in Cellular and Infection Microbiology, 2024)
Pseudomonas aeruginosa has already been stipulated as a "critical" pathogen, emphasizing the urgent need for researching and developing novel antibacterial agents due to the multidrug resistance. Bacterial biofilm formation facilitates cystic fibrosis development and restricts the anti-bacterial potential of many current antibiotics. The capacity of P. aeruginosa to form biofilms and resist antibiotics is closely correlated with quorum sensing (QS). Bacterial QS is being contemplated as a promising target for developing novel antibacterial agents. QS inhibitors is apromising strategy for treating chronic infections. This study reported that the active compound PT22 (1H-pyrrole-2,5-dicarboxylic acid) isolated from Perenniporia tephropora FF2, one endophytic fungus from Areca catechu L., presents QS inhibitory activity against P. aeruginosa. Combining with gentamycin or piperacillin, PT22 functions as a novel antibiotic accelerant against P. aeruginosa. PT22 (0.50, 0.75, and 1.00 mg/mL) reduces the production of QS related virulence factors, such as pyocyanin, rhamnolipid, and inhibits biofilm formation of P. aeruginosa PAO1 instead of affecting its growth. The architectural disruption of the biofilms was confirmed by visualization through scanning electron microscope (SEM) and confocal laser scanning microscopy (CLSM). Real-time quantitative PCR (RT-qPCR) indicated that PT22 significantly attenuated expression of QS-related genes followed by docking analysis of molecules against QS activator proteins. PT22 dramatically increased the survival rate of Galleria mellonella. The PT22 combining with gentamycin or piperacillin present significant inhibition of biofilm formation and eradication of mature biofilm compared to monotherapy which were also confirmed by visualization through SEM and CLSM. After treated with PT22 combining with gentamycin or piperacillin, the survival rates of G. mellonella were significantly increased compared to monotherapy. PT22 significantly enhanced the susceptibility of gentamycin and piperacillin against P. aeruginosa PAO1. Our results suggest that PT22 from P. tephropora FF2 as a potent QS inhibitor, is the candidate as an antibiotic accelerant to combat the antibiotic resistance of P. aeruginosa.